Integrating a quality improvement experiential platform into medical student education - Amy S. Stanley; René M. Kronlage; Miranda J. Reid; Hannah G. Rains; Colleen J. Kalynych; Michele N. Lossius; Janice A. Taylor; Carolyn K. Holland (BMC Medical Education)
Abstract Background The call for quality improvement and patient safety (QI/PS) education has increased at every level of medical education. Here, the authors present a QI/PS experiential platform implemented at the University of Florida College of Medicine (UFCOM). The project established a peer-taught hands-on learning platform in a student-run clinic allowing participants to learn and apply QI/PS concepts and tools in a real-world clinic environment. The aims were to assess students’ perceptions in regard to (1) student confidence in quality improvement (QI) methodology, and (2) competency in executing QI initiatives in healthcare as measured by a post-participation survey. Method A medical student-led quality improvement team was embedded within University of Florida’s (UF’s) existing student-run clinic network. The QI/PS student-team collaborated with clinic leaders and utilized QI/PS tools to establish, monitor, and expand impactful Plan-Do-Study-Act (PDSA) cycles. The impact of the training was then evaluated using The New World Kirkpatrick Model leveraging a post-project survey which included the Beliefs, Attitudes, Skills, and Confidence in Quality Improvement (BASiC-QI) survey and questions on overall student perceptions. Results This project demonstrated positive results in all four levels of Kirkpatrick evaluation: (1) Reaction, (2) Learning, (3) Behavior, and (4) Results. This was shown through (1) a voluntary feedback survey that reported positive feedback from participants with 93% of respondents indicating they “strongly agreed” or “agreed” to positive perception questions; (2) significantly higher scores (p < 0.001) on the BASiC-QI Scale for project participants vs. non-participants; (3) the completion of 4.25 PDSA cycles per QI team; and (4) a 10.1% reduction in median patient time in clinic. Conclusions This study supports the utility of incorporating a student-led QI/PS interactive platform into student-run clinics to increase knowledge and attitude in implementing QI/PS endeavors while simultaneously improving clinic metrics and outcomes for patients.